The factor that influences the agent’s performance in MAA Assurance Bhd and MAA Takaful Bhd / Nur Musyarrafah Daud - Daud, Nur Musyarrafah (Faculty of Business and Management, 2010)
Most people have their first contact with an insurance company through an insurance sales agent. These workers help individuals, families, and businesses select insurance policies that provide the best protection for their lives, health, and property. Insurance sales agents, commonly referred to as “producers” in the insurance industry, sell one or more types of insurance, such as property and casualty, life, health, disability, and long-term care. Property and casualty insurance agents sell policies that protect individuals and businesses from financial loss resulting from automobile accidents, fire, theft, storms, and other events that can damage property. For businesses, property and casualty insurance can also cover injured workers' compensation, product liability claims, or medical malpractice claims. Life insurance agents specialize in selling policies that pay beneficiaries when a policyholder dies. Depending on the policyholder's circumstances, a cash-value policy can be designed to provide retirement income, funds for the education of children, and other benefits, as well. Life insurance agents also sell annuities that promise a retirement income. Health insurance agents sell health insurance policies that cover the costs of medical care and loss of income due to illness or injury. They also may sell dental insurance and short-term and long-term-disability insurance policies. Agents may specialize in any one of these products, or function as generalists, providing multiple products to a single customer. An increasing number of insurance sales agents offer their clients advice on how to minimize risk as well as comprehensive financial planning services, especially to those approaching retirement. These services include retirement planning, estate planning, and assistance in setting up pension plans for businesses. As a result, many insurance agents are involved in “cross-selling” or “total account development.” Besides offering insurance, these agents may become licensed to sell mutual funds, variable annuities, and other securities. This practice is most common with life insurance agents who already sell annuities, but many property and casualty agents also sell financial products. Insurance sales agents also prepare reports, maintain records, and seek out new clients. In the event that policy holders experience a loss, agents help them settle their insurance claims. Insurance sales agents working exclusively for one insurance company are referred to as captive agents. These agents typically have a contractual agreement with the carrier, and are usually an employee of the carrier. Independent insurance agents, or brokers, are mostly facilitators who represent several companies. They match insurance policies for their clients with the company that offers the best rate and coverage. Technology specifically, the Internet has greatly affected the insurance business, making the tasks of obtaining price quotes and processing applications and service requests faster and easier. The Internet has made it easier for agents to take on more clients and to be better informed about new products. It has also altered the relationship between agent and client. Agents formerly used to devote much of their time to marketing and selling products to new clients. Now, clients are increasingly obtaining insurance quotes from a company's Web site and then contacting the company directly to purchase policies. This interaction gives the client a more active role in selecting their policy, while reducing the amount of time agents spend seeking new clients. Insurance sales agents also obtain many new accounts through referrals, so it is important that they maintain regular contact with their clients to ensure that the client’s financial needs are being met. Developing a satisfied clientele that will recommend an agent's services to other potential customers is a key to success for agents. Increasing competition in the insurance industry has spurred carriers to find new ways to keep their clients satisfied. One solution is hiring customer service representatives who are accessible 24 hours a day, 7 days a week to handle routine tasks such as answering questions, making changes in policies, processing claims, and selling more products to clients. The opportunity to cross-sell new products to clients will help an agent’s business grow. The use of customer service representatives also allows agents to concentrate their efforts on seeking out new clients and maintaining relationships with old ones